Influence and interaction of iron and cadmium on photosynthesis and antioxidative enzymes in two rice cultivars. (March 2017) - Liu, Houjun; Zhang, Chengxin; Wang, Junmei; Zhou, Chongjun; Feng, Huan; Mahajan, Manoj D.; Han, Xiaori
Abstract: In this study, a soil pot experiment was conducted to investigate the changes in photosynthesis and antioxidative enzymes in two rice varieties (Shendao 6 and Shennong 265) supplied with iron (Fe), cadmium (Cd), and Fe and Cd together. The concentrations of Fe and Cd in the soil were 0, 1.0 g Fe·kg −1 and 0, 2.0 mg Cd·kg −1, respectively. Photosynthetic indices and antioxidative enzyme activities were recorded at different rice growth stages. At the early stage, Cd showed a transient stimulatory effect on the photosynthetic rate of Shennong 265. For Shendao 6, however, Cd showed a transient stimulatory effect on photosynthetic rate, intercellular CO2 concentration, stomatal conductance and transpiration efficiency. In addition, the results show that Cd can also enhance the superoxide dismutase (SOD) and peroxidase (POD) activities, but reduce the malondialdehyde (MDA) and soluble protein contents in the two rice cultivars. Subsequently, Cd starts to inhibit photosynthesis and SOD activity until the ripening stage, causing the lowest photosynthetic rate and SOD activity at this stage. In contrast, Fe alleviates the Cd-induced changes at earlier or later growth stage. Notably at the later growth stage, the results show that the interaction between Fe and Cd increases the SOD and catalase (CAT) activities, while decreasing the lipid peroxidation and promoting photosynthesis. As a result, it ultimately increases the biomass. The results from this study suggest that Fe (as Fe fertilizer) is a promising alternative for agricultural use to enhance the plant development and, simultaneously, to reduce Cd toxicity in extensively polluted soils. Highlights: Cd has negative influence on the photosynthesis and the formation of biomass in rice. Fe can alleviate the Cd-induced changes at early and later growth stages of two rice varieties. Fe is greatly beneficial for the rice development under Cd-polluted environment.